A Simplified Agent Based Model of a Sinks and Faucets Resource Economy, Using a blind commitment market - Dalsmo, Anton (My University, 2014)
This masters thesis seeks to model a simple financial system by using an agent based model. It seeks to do this by constructing an as simple as possible market and agent dynamic. To do this the blind commitment market is introduced and the general model constructed around this. For this model a number of questions are then posed concerning the model's stability and effectiveness at modelling the core market dynamics. Further- more an analytical analog is created in order to analyse the equilibrium dynamics. From the analytical representation parallels are drawn to the agent based model. The agent based model is constructed in such a way that agents are encouraged to interact in order to meet all demands. The arising dependancy network of agents is then analysed using a graphical representation, which shows how much the different agents depend on each other. The general dynamics are also examined as the three main parameters of the model are varied. It is shown that the bind commitment market upholds supply and demand char- acteristics, and that the agent based model functions as an economy with cooperating agents, however these agents are not making any profit. Furtheromre it is shown that the analytical model is stable for all possible parameters of the allowed parameter space in the sense that feedback processes steer the supply and demand dynamics to a stable fix point, an equilibrium price. The agent based model also gravitates towards an equi- librium price, however minority game dynamics prevent the system from reaching, or staying, at the equilibrium price for long. The minority game dynamics ing the system away from the stable point, causing the system to restart its trajectory towards the equilibrium price, aided by the feedback processes. Lastly the three main parameters of the model are examined with respect to how much they influence the stability of prices inside the model.
Keywords: Grundläggande vetenskaper; Datavetenskap (datalogi); Teknisk fysik; Basic Sciences; Computer Science; Engineering physics